Evaluating the Possibility of Replacing Natural Fine Aggregates in Concrete with Recycled Aggregates - Nguyen, D. D.; Nguyen, D. T.; Cao, T. H.; Phan, V. T. (Engineering, Technology & Applied Science Research, 2021)
This paper presents an investigation on the possibility of replacing natural fine aggregates with recycled aggregates in concrete. The studied recycled aggregates were acquired from crushed waste concrete from demolishing works. The rate of replacement of natural fine aggregates was 10%, 20%, and 30% by weight. Compressive and flexural tensile strength of concrete incorporating recycled aggregates was investigated at 28 days of curing. The results show that the compressive and flexural strength of concrete is strongly affected by the percentage of recycled aggregates. It has been found that the strength decreases linearly with increasing recycled aggregate content. So, in order to apply recycled waste to concrete as fine aggregates, it is necessary to perform supplement research with appropriate additives to compensate for the loss of compressive and flexural strength.